# Calculator search results

Formula
Solve the equation
Graph
$y = 0.3 - \dfrac { 1 } { 5 } \left ( x - 2 \right )$
$y = 0$
$x$Intercept
$\left ( \dfrac { 7 } { 2 } , 0 \right )$
$y$Intercept
$\left ( 0 , \dfrac { 7 } { 10 } \right )$
$0.3- \dfrac{ 1 }{ 5 } \left( x-2 \right) = 0$
$x = \dfrac { 7 } { 2 }$
 Solve a solution to $x$
$0.3 \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 5 } } \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) = 0$
 Multiply each term in parentheses by $- \dfrac { 1 } { 5 }$
$0.3 \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 5 } } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 5 } } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) = 0$
$\color{#FF6800}{ 0.3 } - \dfrac { 1 } { 5 } x - \dfrac { 1 } { 5 } \times \left ( - 2 \right ) = 0$
 Convert decimals to fractions 
$\color{#FF6800}{ \dfrac { 3 } { 10 } } - \dfrac { 1 } { 5 } x - \dfrac { 1 } { 5 } \times \left ( - 2 \right ) = 0$
$\dfrac { 3 } { 10 } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 5 } } \color{#FF6800}{ x } - \dfrac { 1 } { 5 } \times \left ( - 2 \right ) = 0$
 Calculate the multiplication expression 
$\dfrac { 3 } { 10 } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { x } { 5 } } - \dfrac { 1 } { 5 } \times \left ( - 2 \right ) = 0$
$\dfrac { 3 } { 10 } - \dfrac { x } { 5 } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 5 } } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) = 0$
 Calculate the product of rational numbers 
$\dfrac { 3 } { 10 } - \dfrac { x } { 5 } + \color{#FF6800}{ \dfrac { 2 } { 5 } } = 0$
$\color{#FF6800}{ \dfrac { 3 } { 10 } } - \dfrac { x } { 5 } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 2 } { 5 } } = 0$
 Find the sum of the fractions 
$\color{#FF6800}{ \dfrac { 7 } { 10 } } - \dfrac { x } { 5 } = 0$
$\color{#FF6800}{ \dfrac { 7 } { 10 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { x } { 5 } } = \color{#FF6800}{ 0 }$
 Multiply both sides by the least common multiple for the denominators to eliminate the fraction 
$\color{#FF6800}{ \dfrac { 7 } { 2 } } \color{#FF6800}{ - } \color{#FF6800}{ x } = \color{#FF6800}{ 0 }$
$\color{#FF6800}{ \dfrac { 7 } { 2 } } - x = 0$
 Move the constant to the right side and change the sign 
$- x = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 7 } { 2 } }$
$\color{#FF6800}{ - } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 7 } { 2 } }$
 Change the sign of both sides of the equation 
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 7 } { 2 } } \right )$
$x = \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } \dfrac { 7 } { 2 } \right )$
 Simplify Minus 
$x = \dfrac { 7 } { 2 }$
 그래프 보기 
Graph
Solution search results